Aprendizajes basados en retos en la formación previa y continua de estudiantes de pedagogía para educación básica alternativa - Rodríguez de los Ríos, Luis Alberto (2020)
The progress of a research project is presented, in its phase of cabinet work on learning based on challenges to be experienced with students from a university training program in alternative basic education.Pedagogy as a science of education welcomes other successful practical disciplines, one is the challenge-based learning technique-CBL-, that changes the currently dominant frontist learning sessions in ABE. As such, it can be applied to various educational situations in institutions, in the case of the teaching / learning process of previous and continuous professional training of teachers for this modality. The main idea of ​​the technique, the students build a relevant challenge / problem in the community, advance their research and communicate the results through digital means, as well as use the protocols for future applications, this is achieved in the four-phase sessions: the challenge, research, results and communication. The technique has benefits as limitations.